EVALUATION OF TIMSS AND PISA TYPE MATHEMATICS LEARNING - Novia Sandra, Nabila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2026)
Assessment is the process of giving or determining value to a particular object based on certain criteria (Sudjana, 2006). According to Merrens and Lehmans in Purwanto (2006) assessment is a process of planning, obtaining and completing information that is very necessary to make alternative decisions. Winkel (2009:535) argues that assessment is the determination of the level of quality of student achievement based on certain norms, benchmarks, or criteria. The objectives of the study are 1) to describe the steps in implementing student ability tests in solving TIMSS and PISA type mathematics problems in junior high schools, 2) to describe the results of the analysis of students' ability to solve TIMSS and PISA type mathematics problems, 3) to describe the supporting and inhibiting factors for students in solving TIMSS and PISA type mathematics problems. This study took place at SMP Negeri 1 Sidomulyo. The data sources were students of class IXC. The research techniques used were observation, interviews, and tests. The results of the study 1) the steps for implementing the student's ability test to solve TIMSS and PISA type Mathematics problems in students of SMP Negeri 1 Sidomulyo can be known by the stages of preparation, data collection, analysis and students' ability to work on TIMSS and PISA type Mathematics problems and analyzing abilities into categories based on literacy and levels that have been made, 2) the results of the analysis of students' ability to solve PISA type Mathematics problems include groups of mathematical content mastery abilities, mathematical process mastery abilities and mathematical context mastery abilities to solve TIMSS and PISA type Mathematics problems, 3) supporting factors for readiness, student abilities, PMRI approach and the material taught. Inhibiting factors, question variations, test implementation and selected materials.